PENGEMBANGAN PINK MIANA MENJADI PRODUK UNGGULAN DAERAH BERBASIS IPTEK UNTUK MEWUJUDKAN KESEJAHTERAAN MASYARAKAT DI DESA PUNTUKREJO - Farhan F. A.; Fortuna R. A; Firman D; Dora A. F.; Dila R.; Ruben H. A.; Niko Dias S. P.; Trisya K. M.; Rysca Indreswari; Fakhrul Fathoni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Pink Miana plant (Coleus scuttelarioides) is a miana variety that is only cultivated in one of the tourism msmes The Lawu Fresh, Puntukrejo Ngargoyoso Village, Karanganyar, Central Java. This ornamental plant, which is famous for its unique leaf color, turns out to contain various substances such as antioxidants and anti-inflammatories that are good for the body's immunity. However, the abundance of potential possessed by Miana is not balanced with the capabilities of the local community in its processing. Improper processing of Pink Miana can lead to reduced or loss of content of these substances if processed with too hot temperatures. The method used in solving these problems is controlled boiling. Controlled boiling is a method of boiling using low heat with regular temperature monitoring so as not to exceed the maximum temperature that the material can accept. The findings obtained are syrup products made from the first miana leaves